2023
DOI: 10.21203/rs.3.rs-2581503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Propensity score-matched analysis of oncological and functional outcomes of submental island flap versus radial forearm free flap for oral cavity cancer reconstruction

Abstract: Background The aim of this study is to compare the oncological and functional outcomes of the submental island flap versus the radial forearm free flap used for oral cavity cancer reconstruction after minimizing differences in baseline characteristics. Methods Propensity scores for each oral cavity cancer patients who underwent surgical resection and immediate reconstruction with a submental island flap or a radial forearm free flap with a flap size ≤ 60 cm2 between October 2008 and December 2021 were gener… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Since Martin et al introduced SF [10], it has a broad rotation arc and may reach defects in the upper airway [13], the oral cavity [14], oropharynx [15], nasopharynx[16], and skull base [4] et al Previous research[8, 17,18] has demonstrated that the application of SF for head and neck reconstruction has several bene ts, such as being simple to harvest during the same surgical procedure, having exible rotation and being close to sites of head and neck defects, resulting in less trauma and complications, a good quality of life following surgery, requiring less time and money than free tissue transfer without signi cantly affecting functional outcomes or complication rates, and having donor site scarring that can be easily hidden behind the mandible with good aesthetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Since Martin et al introduced SF [10], it has a broad rotation arc and may reach defects in the upper airway [13], the oral cavity [14], oropharynx [15], nasopharynx[16], and skull base [4] et al Previous research[8, 17,18] has demonstrated that the application of SF for head and neck reconstruction has several bene ts, such as being simple to harvest during the same surgical procedure, having exible rotation and being close to sites of head and neck defects, resulting in less trauma and complications, a good quality of life following surgery, requiring less time and money than free tissue transfer without signi cantly affecting functional outcomes or complication rates, and having donor site scarring that can be easily hidden behind the mandible with good aesthetic effect.…”
Section: Discussionmentioning
confidence: 99%